PROLONGED DUAL ANTIPLATELET THERAPY AFTER MYOCARDIAL INFARCTION: WHAT THE RESULTS OF THE PEGASUS-TIMI 54 TRIAL SHOW - I. S. Yavelov (Столичная издательская компания, 2017)
Prerequisites for the prolonged dual antiplatelet therapy after myocardial infarction are presented. The results of a large randomized placebo-controlled PEGASUS-TIMI 54 trial on the evaluation of efficacy and safety of prolonged use of a combination of acetylsalicylic acid and blocker P2Y12 platelet receptor, ticagrelor, in patients with high risk of thrombotic complications of atherosclerosis with a history of myocardial infarction 1-3 years ago are considered. The contribution of the results of this clinical trial in the modern understanding of the optimal use of antiplatelet agents in patients after myocardial infarction is analyzed.